Can Serum Neutrophil-to-Lymphocyte Ratio Be a Predictive Biomarker to Help Differentiate Active Chronic Otitis Media From Inactive Chronic Otitis Media?. Issue 3 (May 2017) - Tansuker, Hasan Deniz; Eroğlu, Sinan; Yenigün, Alper; Taşkin, Ümit; Oktay, Mehmet Faruk
Abstract : Objectives: The authors' aim was to investigate whether serum neutrophil to lymphocyte ratio might be used as a predictive biomarker to help differentiate active from inactive chronic otitis media (COM). Methods: Two hundred fifty-nine patients having inactive COM received tympanoplasty without mastoidectomy and were identified as Group 1. On the other hand, 254 patients having active COM received tympanoplasty with mastoidectomy and were identified as Group 2. Routine hemogram tests were performed preoperatively for both the groups. By performing a chart review, white blood cell count, red blood cell count, hemoglobin, hematocrit, platelet, and mean platelet volume values were compared between the groups in an age-matched and sex-matched manner. Results: A total of 513 COM patients with age range of 7 to 65 years were included in the study. Two hundred seventy-five patients (53.6%) were male, 238 were (46.4%) female. Preoperatively both serum neutrophil and lymphocyte counts were significantly higher in Group 2 ( P  = 0.015 and P  = 0.004, respectively). However, the neutrophil-to-lymphocyte ratios between the groups were not significantly different ( P  = 0.511). Conclusion: No statistically significant differences were identified from preoperative neutrophil-to-lymphocyte ratios between patients having active COM and inactive COM. Level of evidence: Level NA.